PK Pak Tuition Centre Management System using Mobile Application - P'NG, HOOI YIN; Ramli, Azizul Azhar (Applied Information Technology And Computer Science, 2022)
The PK Pak Tuition Centre Management System is a system which can use to manage the tuition centre in a computerized way. Nowadays, most of the tuition centre lacks a computerized management system for their tuition centre and still manages their tuition centre in a traditional way by using pen-paper and files based. Therefore, a computerized management system is needed to manage the tuition centre in a systematically way. The prototyping-based methodology is used as the methodology to develop this system. Besides, the development of the PK Pak Tuition Center Management System will be done using Android Studio and Java programming language. Lastly, this proposed system will address the tuition centre's management problems by allowing administrators to manage the tuition centre more efficiently and reduce their workload and help them save more time and expenses in managing the centre.